Tumor infiltration by Tbet+ effector T cells and CD20+ B cells is associated with survival in gastric cancer patients. (1st February 2016) - Hennequin, Audrey; Derangère, Valentin; Boidot, Romain; Apetoh, Lionel; Vincent, Julie; Orry, David; Fraisse, Jean; Causeret, Sylvain; Martin, François; Arnould, Laurent; Beltjens, Françoise; Ghiringhelli, François; et al.
Abstract : Tumor-infiltrating T and B lymphocytes could have the potential to affect cancer prognosis. The objective of this study was to investigate the prognostic significance of tumor infiltration by CD8 and CD4 T cells, and B lymphocytes in patients with localized gastric cancer. In a retrospective cohort of 82 patients with localized gastric cancer and treated by surgery we quantitatively assessed by immunohistochemistry on surgical specimen, immune infiltrates of IL-17 +, CD8 +, Foxp3 +, Tbet + T cells and CD20 + B cells both in the tumor core and at the invasive margin via immunohistochemical analyses of surgical specimens. We observed that CD8 + and IL17 + T-cell densities were not significantly associated with gastric cancer prognosis. In contrast, high infiltration of Tbet + T cells, high numbers of CD20 + B-cell follicles, and low infiltration of Foxp3 + T cells, were associated with better relapse-free survival. Interestingly, treatment with neoadjuvant chemotherapy or histological tumor type (diffuse versus intestinal) did not influence type and density of immune infiltrates or their prognostic value. Immunohistochemical analysis of the gastric cancer stromal microenvironment revealed organized T and B cell aggregates, with strong structural analogies to normal secondary lymphoid organs and which could be considered as tertiary lymphoid structures. Using transcriptomic data from an independent cohort of 365 localized gastric cancer, we confirmed that a coordinated Th1, and B cell stromal gene signature is associated with better outcome. Altogether, these data suggest that tumor infiltration by B and Th1 T cells could affect gastric cancer prognosis and may be used to better define the outcome of patients with localized gastric cancer.